Photobiomodulation and photodynamic therapy applied after electrocauterization for skin healing optimization in rats. Issue 5 (7th February 2022) - do Amparo Manoel, Cecília; de Sousa Mariano, Samara; da Silva Ramos, Ericsson; Paolillo, Fernanda Rossi; de Aro, Andrea Aparecida; Mendes, Carolini; Venturini, Ligia Milanez; Silveira, Paulo Cesar Lock; Bagnato, Vanderlei Salvador; de Andrade, Thiago Antônio Moretti
Abstract: Photobiomodulation‐PBM and Photodynamic Therapy‐PDT have been used to induce healing. However, the effects of these therapies on skin‐lesions induced by electrocautery are unknown, aiming at more favorable clinical and esthetic results. Electrocauterization was done in 78‐female Wistar‐rats using a system that includes an electrocautery and red‐LED. The groups were: No injury, Injury, Injury + ALA (topical 5‐aminolevulinic acid application), Injury + LED and Injury + ALA + LED (topical ALA application followed by photoactivation with LED). After 2nd, 7th and 14th days post‐injury, immuno‐histomorphometric analyses (inflammatory infiltrate, blood vessels, fibroblasts, eschar/epidermal thickness, IL‐10 and VEGF) and biochemical assays of MPO (neutrophil), NAG (macrophage), nitrite, DCF (H2 O2 ), carbonyl (membrane's damage), sulfhydryl (membrane's integrity), SOD, GSH, hydroxyproline and re‐epithelialization area were performed. The Injury + LED and Injury + ALA + LED groups controlled inflammation and oxidative stress, favoring angiogenesis, fibroblasts proliferation and collagen formation. Therefore, the PBM or PDT was effective in tissue formation with thinner eschar and epidermis, resulting in less scarring after electrocauterization. Abstract : Photodynamic Therapy (PDT) with topical administration of 3% ALA and red LED, as well as Photobiomodulation (PBM) with red LED were applied after eletrocauterization in rats. There were modulation of inflammatory process and control of oxidative damage at different phases of healing. These effects conduced to angiogenesis, fibroblasts proliferation and collagen formation, accelerating the skin healing process. It indicates the potential of these both protocols for medical and esthetic treatments.